Inhibitors of human collagenase, MMP1 - Leite, Sergio Roberto de Andrade (Eclética Química, 2009)
Different common drugs (Meloxicam, Tenoxicam and Piroxicam, and sodium alendronate) were tested both experimental and theoretically as inhibitors of interstitial human collagenase, also known as matrix metalloproteinase 1 (MMP-1). The in vitro collagenase activity, alone and in the presence of inhibitors, was quantified by the reaction with a fluorescent synthetic substrate and measuring the change of emission. Collagenase-inhibitor interaction was studied theoretically by computational calculations. Three among the four tested substances showed moderate inhibiting activity against the human collagenase.